KONSEP SULH DAN TAHKIM SEBAGAI ALTERNATIF DALAM UPAYA PENYELESAIAN SENGKETA EKONOMI SYARIAH DI ERA MODERN - Vahlevi, Dewi Riza Lisvi (Jurnal Ekonomi Syariah Darussalam, 2021)
Sharia economic growth in this era has grown very rapidly. With such a significant development, many disputes have arisen. This makes it difficult for many people to find a way out of this problem. At the time of the Messenger of Allah, dispute resolution was usually carried out by means of sulh and tahkim. And in this writing, the author limits two main problems; First, how is the concept of sulh and tahkim in dispute resolution. And second, how to implement sulh and tahkim in dispute resolution in this modern era. The purpose of this paper is to find out the application of problem solving in accordance with good Islamic law. This type of research is library research with a normative and juridical approach. And the results of this study found that (1) the concept of sulh is to reconcile the two parties to the dispute, if it is felt that peace does not get results, then the tahkim method is carried out, namely by resolving disputes properly. (2) In this modern era, sulh is carried out by means of peace while tahkim is carried out by means of arbitration.